Distribution of Dune Landform on Mars - Chao, Li; Zhibao, Dong (Frontiers in Astronomy and Space Sciences, 2022)
Dune landforms are widely distributed on Mars and contain abundant information about the Martian atmosphere and sedimentary environment. At present, the understanding of Martian dunes and their environmental significance still needs to be further excavated. Sand dunes were investigated on a global scale using high-resolution remote sensing imagery covering Mars, supported by GIS technology. The object of this paper is to obtain dune landform information and analyze its distribution characteristics and patterns. The results indicated that the Martian dunefields are scattered, generally small in scale and spatially distinct. They are mainly concentrated in high-latitude and polar regions, and show latitude zonality. Similar to Earth, Martian dunes are mainly located in low-lying geomorphic units that are conducive to the accumulation of sand. We propose that the limited sand supply is an important feature of the Martian dune development conditions. The scattered distribution of dune fields reflects the lack of loose sediments on Mars as a whole, which provides an important clue to understanding the Martian environment and evolutionary history.